(untitled) (Pedagogy of Higher and Secondary Education, 2012)
У статті автор дає обґрунтування сегменту спілкування в структурі педагогічної культури майбутнього вчителя, багатоплановому процесі організації, встановленні і розвитку контактів, взаєморозумінні і взаємодії між майбутнім учителем і учнем. Ключові слова: сегмент спілкування, педагогічна культура. In the given article the author presents the basic structural laws of the pedagogical culture of a teacher to be and their influence on the planning, organizing and developing contacts between future teachers and pupils in the spirit of improving their further mutual understanding and cooperation. Key words: structural laws, pedagogical culture.